2015
DOI: 10.1016/j.bandc.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Easy to learn, hard to suppress: The impact of learned stimulus–outcome associations on subsequent action control

Abstract: The inhibition of impulsive response tendencies that conflict with goal-directed action is a key component of executive control. An emerging literature reveals that the proficiency of inhibitory control is modulated by expected or unexpected opportunities to earn reward or avoid punishment. However, less is known about how inhibitory control is impacted by the processing of task-irrelevant stimulus information that has been associated previously with particular outcomes (reward or punishment) or response tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 77 publications
(109 reference statements)
1
13
3
Order By: Relevance
“…In addition, both groups learned to withhold action to avoid punishment more effectively than to withhold action to gain reward. These patterns replicate previous studies using a similar paradigm in healthy adults (van Wouwe et al, 2015; Wagenbreth et al, 2015; Chowdhury, Guitart-Masip, Lambert, Dayan, et al, 2013; Chowdhury, Guitart-Masip, Lambert, Dolan, et al, 2013; Guitart-Masip, Chowdhury, et al, 2012; Guitart-Masip, Huys, et al, 2012). Our findings also replicate improved outcomes on learning to withhold to gain reward with DA as found in a levodopa study in HCs by Guitart-Masip et al (2014).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, both groups learned to withhold action to avoid punishment more effectively than to withhold action to gain reward. These patterns replicate previous studies using a similar paradigm in healthy adults (van Wouwe et al, 2015; Wagenbreth et al, 2015; Chowdhury, Guitart-Masip, Lambert, Dayan, et al, 2013; Chowdhury, Guitart-Masip, Lambert, Dolan, et al, 2013; Guitart-Masip, Chowdhury, et al, 2012; Guitart-Masip, Huys, et al, 2012). Our findings also replicate improved outcomes on learning to withhold to gain reward with DA as found in a levodopa study in HCs by Guitart-Masip et al (2014).…”
Section: Discussionsupporting
confidence: 89%
“…The action–valence paradigm also offers a novel tool for investigating the effects of pharmacologic and surgical interventions (e.g., deep brain stimulation) aimed at modulating BG activity selectively. We recently demonstrated that implicit processing of already formed natural and unnatural action–valence associations, even when irrelevant to a current task, produces dissociable effects on cognitive control mechanisms (van Wouwe et al, 2015). How established action–valence learning and biases interact with cognitive control mechanisms that are also linked to frontal BG circuits could provide new insight into a range of behavioral deficits involving poor control over strong urges and impulses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations